2021
DOI: 10.1111/1750-3841.15689
|View full text |Cite
|
Sign up to set email alerts
|

Development of quaternary nanocomposites made up of cassava starch, cocoa butter, lemongrass essential oil nanoemulsion, and brewery spent grain fibers

Abstract: We report on production of novel quaternary nanocomposite films based on thermoplastic starch (TPS, 8% w/v) derived from cassava, cocoa butter, (CB, 30% wt.%), and lemongrass essential oil (LEO, 1:1) nanoemulsions reinforced with different concentrations of brewery spent grain (BSG, 5 or 10 wt.%) fibers, by continuous casting. The chemical composition, the morphological, thermal, mechanical properties, film barrier, biodegradability in the vegetable compound, in addition to the application in chocolates, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 116 publications
(172 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, the FT-IR spectrum of the LNE alone gives an intense peak from 1671 to 1731 cm −1 which was assigned to the C�O stretch of methyl esterified carboxyl groups, evident of the aromatic group of compounds. 41 As is expected, these intense peaks are also overserved for the two nanocomposites NC1 and NC2 but not for AgNPs. Thielmann et al 42 have confirmed that the presence of citral and limonene groups as evidenced by peaks 1600 and 1735 cm −1 in lemongrass oil are responsible for the antimicrobial activity.…”
Section: Characterization Of the Nanocompositesupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, the FT-IR spectrum of the LNE alone gives an intense peak from 1671 to 1731 cm −1 which was assigned to the C�O stretch of methyl esterified carboxyl groups, evident of the aromatic group of compounds. 41 As is expected, these intense peaks are also overserved for the two nanocomposites NC1 and NC2 but not for AgNPs. Thielmann et al 42 have confirmed that the presence of citral and limonene groups as evidenced by peaks 1600 and 1735 cm −1 in lemongrass oil are responsible for the antimicrobial activity.…”
Section: Characterization Of the Nanocompositesupporting
confidence: 66%
“…Stretches at 1650 cm –1 , 1386 cm –1 , and 1074 cm –1 in the spectrum of AgNPs are attributed to CO, O–H, and C–O functional moieties, respectively, confirming a strong interaction between citrate and AgNPs. Furthermore, the FT-IR spectrum of the LNE alone gives an intense peak from 1671 to 1731 cm –1 which was assigned to the CO stretch of methyl esterified carboxyl groups, evident of the aromatic group of compounds . As is expected, these intense peaks are also overserved for the two nanocomposites NC1 and NC2 but not for AgNPs.…”
Section: Resultsmentioning
confidence: 53%
“…Similarly, Norcino et al 127 observed no effect of copaiba oil nanoemulsions on the biodegradability of pectin films determined by respirometry tests at 28 °C. Mendes et al 128 also did not observe an effect of the incorporation of nanoemulsified lemongrass essential oil on the biodegradability of films based on cassava starch, cocoa butter, and reinforced with brewery spent grain fibers.…”
Section: Application Of Active Films Incorporated With Emulsions-base...mentioning
confidence: 93%
“…Regarding the effect of emulsions on the biodegradability of active lms, Mendes et al 53 observed that the biodegradability of the cassava starch-based lms determined in vegetal compost (soil) was not qualitatively affected by the addition of lemongrass essential oil emulsions. Similarly, Norcino et al 127 observed no effect of copaiba oil nanoemulsions on the biodegradability of pectin lms determined by respirometry tests at 28 C. Mendes et al 128 also did not observe an effect of the incorporation of nanoemulsied lemongrass essential oil on the biodegradability of lms based on cassava starch, cocoa butter, and reinforced with brewery spent grain bers.…”
Section: Chemical Stability and Biodegradability Of Active Lms Loaded With Nanoemulsionsmentioning
confidence: 95%